Observation Of Diaphragm Wall As Retaining Wall In The Leuwikeris Area - Nur Jannati Samad; Mahfuz Hudori (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The leuwikeris dam area was a rural area near the river. The main dam of this project is located in Ancol Village, Cineam District, Tasikmalaya Regency, and West Java Province. Leuwikeris Dam was built by damming the Citanduy river which has upstream rivers in the Cakrabuana mountains and downstream rivers in Cilacap Regency. The purpose of this article is to provide an overview of observations, shapes, and configurations of retaining wall structures. Diaphragm wall provides a more minimal seepage effect in other methods such as secant pile. Secant pile has only the same uses but vast area difference. This article tries to give a broad overview of the diaphragma wall of the leuwikeris dam.